RARE CLINICAL CASES OF PRENATAL ULTRASOUND DIAGNOSIS OF PREMATURE CLISURE OF THE FORAMEN OVALE - Людмила Викторовна Абрамова; Евгения Евгеньевна Елисеева; Ирина Леонидовна Матушкова; Ольга Аркадьевна Соловьева; Светлана Леонидовна Стопичева; Елена Владимировна Рудаева; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Кира Борисовна Мозес; Сергей Валерьевич Рыбников; Яэль Центер (The Publishing House Medicine and Enlightenment, 2023)
Intrauterine premature closure of the foramen ovale is a rare pathology. With antenatal closure of the foramen ovale, right ventricular heart failure develops. The severity of the condition of the fetus is determined by the timing of the closure of the oval window. The shorter the gestation period, the more severe the consequences. The diagnostic criterion for premature closure of the foramen ovale is the presence of an intact atrial septum and the absence of communication between the atria. On ultrasound, the pathological nature of the kinetics of the foramen ovale is manifested by a bending of the valve towards the left atrium, and the location of the foramen ovale valve across the atrium with a and b peaks are early signs of premature closure of the foramen ovale. Premature closure of the oval window in the case of an altered nature of valve movement occurs in the presence of effusion and cardiac arrhythmias. Clinical cases of premature antenatal closure of the foramen ovale are presented. There were two pregnant women under observation, at full-term gestation, who were diagnosed with antenatal premature closure of the foramen ovale. The pregnancies ended in timely delivery and the birth of children with normal weight and height parameters, with an Apgar score of 6/7 points.